2018
DOI: 10.1557/adv.2018.412
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Cassava Bark Nanoparticles

Abstract: Synthesis and characterization of cassava bark nanoparticles (CBNPs) was carried out using ball milling at 36, 48, 60 and 72 hours. The morphology study was done using SEM and the Gwyddion software was used to determine the particle sizes from the SEM images. The particle distribution for the un-milled cassava bark (CB) was between 1.25 + 0.06 to 19.92 + 1.00 µm, while after milling for 36, 48, 60 and 72 hours the average particle size were 4.07 + 0.20, 4.00 + 0.20 µm, 80.90 + 4.05, 74.50 + 3.73 nm respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…From the estimated amount of cassava stem waste generated it shows that enough can be obtained for processing into useful application. Cassava stem can be fed to pigs, poultry, dairy cattle [45] and biochar production [46].…”
Section: Cassava Stem (Cs)mentioning
confidence: 99%
See 1 more Smart Citation
“…From the estimated amount of cassava stem waste generated it shows that enough can be obtained for processing into useful application. Cassava stem can be fed to pigs, poultry, dairy cattle [45] and biochar production [46].…”
Section: Cassava Stem (Cs)mentioning
confidence: 99%
“…All of which helps improve the properties of metallic coatings [47,48]. This chapter discuss the synthesis and characterization of CPENPs which can be used as additives to coatings for corrosion protection, especially coatings for oil and gas applications due to the properties as discussed by Kolawole et al [46][47][48]. Therefore, CPENPs should not be left to waste as they are useful for additives in coatings.…”
Section: Synthesis Of Cassava Plant Extract Nanoparticles (Cpenps)mentioning
confidence: 99%
“…The results show that crude oil has the most significant effect of in the rate of corrosion of steel and increased as temperature and fluid velocity increased. Kolawole et al [16] give a comprehensive review of CO 2 and H 2 S corrosion problems in API 5L steel pipeline and the proper methods to control the corrosion problems. They showed that the primary causes of corrosion in oil and gas pipelines are the presence of water together with acid gases (CO 2 and H 2 S).…”
Section: -Introductionmentioning
confidence: 99%